2020
DOI: 10.21203/rs.3.rs-133358/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between prior cardiometabolic therapy and in-hospital mortality in very old patients with type 2 diabetes mellitus hospitalized due to COVID-19. A nationwide observational study in Spain

Abstract: Background Advanced age and diabetes are both associated with poor prognosis in COVID-19. However, the effects of cardiometabolic drugs on the prognosis of diabetic patients with COVID-19, especially very old patients, are not well-known. This work aims to analyze the association between preadmission cardiometabolic therapy (antidiabetic, antiaggregant, antihypertensive, and lipid-lowering drugs) and in-hospital mortality among patients ≥ 80 years with type 2 diabetes mellitus hospitalized for COVID-19. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The included studies were conducted in Austria [14], Belgium [15], China [16][17][18][19][20][21][22][23][24], France [25][26][27], Hong Kong [28], Iraq [29], Italy [30,31], Russia [32]which determines the high relevance of risk factor analysis for outcomes in DM patients to substantiate the strategy for this category of patients. AIM: To assess the effect of clinical and demographic parameters (age, gender, body mass index (BMI, South Korea [33,34], Spain [35,36], UK [37][38][39][40][41] and USA [42][43][44][45].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…The included studies were conducted in Austria [14], Belgium [15], China [16][17][18][19][20][21][22][23][24], France [25][26][27], Hong Kong [28], Iraq [29], Italy [30,31], Russia [32]which determines the high relevance of risk factor analysis for outcomes in DM patients to substantiate the strategy for this category of patients. AIM: To assess the effect of clinical and demographic parameters (age, gender, body mass index (BMI, South Korea [33,34], Spain [35,36], UK [37][38][39][40][41] and USA [42][43][44][45].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…After studies were carefully reviewed based on the inclusion and exclusion criteria, 22 retrospective observational studies were selected for further meta-analysis of metformin use and inhospital mortality. The flowchart for the study selection is shown in Fig 1 . Of these 22 studies, 17 studies reported on the association of outpatient metformin use and in-hospital mortality [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37], 6 studies investigated the link between inpatient metformin use and in-hospital mortality [37][38][39][40][41][42], and 2 study probed the association of both outpatient and inpatient metformin PLOS ONE use and in-hospital mortality [37,42]. There were 16 studies with extractable raw event data.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…The flowchart for the study selection is shown in Figure 1. Of these 19 studies, 14 studies reported on the association of outpatient metformin use and in-hospital mortality [20][21][22][23][24][25][26][27][28][29][30][31][32][33], 4 studies investigated the link between inpatient metformin use and in-hospital mortality [34][35][36][37], and 1 study probed the association of both outpatient and inpatient metformin use and in-hospital mortality [38]. There were 13 studies with extractable raw event data.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%